Sonic Hedgehog (SHH) pathway in the adult brain : key signaling for astrocyte reactivation and brain repair (2016)
ABSTRACT: While neurons play a key role in neurotransmission in the nervous central system (CNS) of animals, glial cells are crucial for neuron support and brain maintenance. Recent studies reveal that glial cells regulate the release and reuptake of neurotransmitters, pyruvate and glutathione metabolism, ion buffering, the organization of blood brain barrier and ensures the production of myelin and cerebrospinal fluid. The activity of glial cells is coordinated by the communication between neurons and the glia. Among cell signals in the brain, Sonic Hedgehog (SHH) pathway plays a key role regulating the development and the patterning of the central nervous system. In the adult brain, SHH has been found to be secreted by neurons and astrocytes, and to regulate in this manner, neuro-glial interactions. Upon brain injury, SHH signaling appears to be (re)- activated in the adult brain and may be related with tissue regeneration. The glial cells and more particularly astrocytes are key cells responding to brain injury and participating in brain repair. Interestingly, astrocyte response is mediated by SHH activation in these cells that elicits diverse cell reactions in the brain leading to neuroprotection and reinforcement of the blood brain barrier upon injury. This review highlights the important role of glial cells and more speci cally of astrocytes in brain physiology, the implication of SHH signaling in brain organization and function, and nally, how SHH signaling regulates astrocyte re-activation and cell response to tissue injury and repair in the brain in the adult organism.